2018
DOI: 10.1029/2018ea000417
|View full text |Cite
|
Sign up to set email alerts
|

Examining Forest Structure With Terrestrial Lidar: Suggestions and Novel Techniques Based on Comparisons Between Scanners and Forest Treatments

Abstract: Terrestrial laser scanners (TLSs) provide a tool to assess and monitor forest structure across forest landscapes. We present TLS methods, suggestions, and mapped guidelines for planning TLS acquisitions at varying scales and forest densities. We examined rates of point‐density decline with distance from two TLS that acquire data at relatively high and low point density and found that the rates were nearly identical between scanners (p value <0.01), suggesting that our findings are applicable to a range of TLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 106 publications
(132 reference statements)
1
14
0
Order By: Relevance
“…A statistical comparison between the measured and estimated diameters showed a significant difference ( p -value < 0.05). The estimated DBHs were consistent with the reference measurements, but DBHs derived from TLS were slightly overestimated [ 61 ] in both plots ( Figure 9 ). In plot 1, the average of the measured diameters was 329.46 mm compared to the estimated value of 339.72 mm.…”
Section: Resultssupporting
confidence: 78%
“…A statistical comparison between the measured and estimated diameters showed a significant difference ( p -value < 0.05). The estimated DBHs were consistent with the reference measurements, but DBHs derived from TLS were slightly overestimated [ 61 ] in both plots ( Figure 9 ). In plot 1, the average of the measured diameters was 329.46 mm compared to the estimated value of 339.72 mm.…”
Section: Resultssupporting
confidence: 78%
“…For this study, we focused on a pure ponderosa pine (Pinus ponderosa) forest near Flagstaff, AZ where we could make use of previously collected ALS and TLS lidar datasets (Figure 2) [18]. These sites were managed by the US Forest Service as part of the "Fire and Fire Surrogate" study network [29] with original treatment objectives including fuels reductions [30].…”
Section: Study Sitementioning
confidence: 99%
“…Mobile laser scanner systems offer a powerful tool to ease the time and labor demands of traditional plot-based sampling while potentially providing accurate and highly precise estimates of basic forest structural conditions [12,13]. While fixed-wing airborne laser scanning (ALS) platforms have been commonplace for decades, more recently, terrestrial and mobile lidar systems have been investigated for characterizing forest structure, as their higher point densities allow for more detailed and robust extraction of structural attributes, subcanopy occlusion of smaller trees and other ecologically important species can be reduced, and their data can be collected more frequently than airborne systems [13,[16][17][18][19][20][21]. While the absolute positional error of points collected by MLS was typically less precise than TLS due to the propagation of positioning errors accumulated during scan registrations (e.g., see Figure 1), MLS made use of localization algorithms (e.g., SLAM; Simultaneous Localization and Mapping), which enabled accurate positioning of the scanner in vegetated environments where GNSS and GPS signals were typically hindered by dense canopies and the movement of MLS may have reduced overall occlusion [13,15,22].…”
Section: Introductionmentioning
confidence: 99%
“…In our study there was a similar placement of plots from different forest types in multivariate space based on ALS and TLS structural diversity metrics. However, there were both similarities and differences in the hierarchical agglomerative clustering by TLS (5 clusters) and ALS (3 clusters is desirable to resolve fine-scale structural variation and its role in forest ecosystem function; for example, to understand differences in local disturbance on the same forest type [24] or to assess the effects of forest management actions [36]. However, previous studies have demonstrated that at larger scales greater variation in structural diversity occurs across forest types and sites rather than within sites [2,18,37].…”
Section: Discussionmentioning
confidence: 99%